Fluidymation: Stylizing Animations Using Natural Dynamics of Artistic Media. (27th November 2021) - Platkevič, A.; Curtis, C.; Sýkora, D.
Abstract: We present Fluidymation—a new example‐based approach to stylizing animation that employs the natural dynamics of artistic media to convey a prescribed motion. In contrast to previous stylization techniques that transfer the hand‐painted appearance of a static style exemplar and then try to enforce temporal coherence, we use moving exemplars that capture the artistic medium's inherent dynamic properties, and transfer both movement and appearance to reproduce natural‐looking transitions between individual animation frames. Our approach can synthetically generate stylized sequences that look as if actual paint is diffusing across a canvas in the direction and speed of the target motion.